2021
DOI: 10.5858/arpa.2020-0671-oa
|View full text |Cite
|
Sign up to set email alerts
|

Patterns of Translocation Testing in Patients Enrolling in a Cooperative Group Trial for Newly Diagnosed Metastatic Ewing Sarcoma

Abstract: Context.— Molecular diagnostics play an increasing role in the diagnosis of Ewing sarcoma. The type of molecular testing used in clinical practice has been poorly described. Objective.— To describe patterns of translocation testing for newly diagnosed Ewing sarcoma. Design.— Children's Oncology Group (COG) trial AEWS1221 was a phase III randomized trial enrol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 16 publications
0
7
0
Order By: Relevance
“…A prior analysis of institutional translocation testing from this trial showed that 14% of patients lacked molecular data supporting the diagnosis. 33 As such, it is possible that patients with histologic mimics of Ewing sarcoma without an established role for IGF-1R inhibition may have enrolled, further diluting any beneficial effect of ganitumab in bona fide Ewing sarcoma (ie, tumors with FET / ETS translocations). Second, there are no validated biomarkers predictive of benefit from IGF-1R inhibition and therefore no enrichment could be performed in our trial.…”
Section: Discussionmentioning
confidence: 99%
“…A prior analysis of institutional translocation testing from this trial showed that 14% of patients lacked molecular data supporting the diagnosis. 33 As such, it is possible that patients with histologic mimics of Ewing sarcoma without an established role for IGF-1R inhibition may have enrolled, further diluting any beneficial effect of ganitumab in bona fide Ewing sarcoma (ie, tumors with FET / ETS translocations). Second, there are no validated biomarkers predictive of benefit from IGF-1R inhibition and therefore no enrichment could be performed in our trial.…”
Section: Discussionmentioning
confidence: 99%
“…10 Multiple studies of sarcomas have demonstrated a significant percent of cases demonstrating discordance between initial pathologic diagnoses and the diagnosis upon second opinion. [11][12][13][14] In the present case, the diagnosis of Ewing sarcoma still relies heavily on EWSR1 translocation detection by FISH, 15 which in the case of cutaneous Ewing sarcoma, can be problematic as it: (1) does not identify the EWSR1 binding partner and (2) can be negative when non-FLI1 Ewing fusion types are present, such as EWSR1-ERG. 16 Cutaneous Ewing sarcomas harboring an EWSR1-ERG fusion are reported in the literature.…”
Section: Discussionmentioning
confidence: 99%
“…FISH was carried out on the primary tumor in three-fourths of the patients. Dubois et al (24) found positive testing for an EWSR1 or FUS translocation in 211, which equates almost 90% of the patients. A reverse transcriptionpolymerase chain reaction (RT-PCR) was carried out in one fifth of the patients.…”
Section: Oncogenetic Origins and Cell Signaling Of Ewing Sarcomamentioning
confidence: 99%
“…is not yet fully studied in detail. In a recent study involving the Children' s Oncology Group (COG) trial AEWS1221, the patterns of translocation testing for newly diagnosed ES were described (24). The AEWS1221 trial was a phase III randomized study enrolling patients with newly diagnosed metastatic ES/ PNET from 2014 to 2019.…”
Section: Oncogenetic Origins and Cell Signaling Of Ewing Sarcomamentioning
confidence: 99%